2018
DOI: 10.5937/22-16620
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical approach of hybrid image classification for land use and land cover mapping

Abstract: Remote sensing data analysis can provide thematic maps describing land-use and land-cover (LULC) in a short period. Using proper image classification method in an area, is important to overcome the possible limitations of satellite imageries for producing land-use and land-cover maps. In the present study, a hierarchical hybrid image classification method was used to produce LULC maps using Landsat Thematic mapper TM for the year of 1998 and operational land imager OLI for the year of 2016. Images were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The Zayanderud Dam watershed gives the highest part of water yield. The average temperature of the basin is 8–13 °C with 350–1250 mm precipitation 23 . This region used to have a significant capacity for livestock grazing, with its primary LU/LC being forests and rangelands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zayanderud Dam watershed gives the highest part of water yield. The average temperature of the basin is 8–13 °C with 350–1250 mm precipitation 23 . This region used to have a significant capacity for livestock grazing, with its primary LU/LC being forests and rangelands.…”
Section: Methodsmentioning
confidence: 99%
“…The destruction of natural forests and rangelands has been driven by economic growth, mainly related to the expansion of agricultural land and build-up development. LUC in the Zayanderud Dam watershed has an incredibly damaging effect on natural forests and rangelands, as well as on the expansion of agricultural and construction areas 23 . The study has concentrated only on the spatial distribution of habitat quality due to time and cost constraints.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid classification approach, for example, maximum likelihood supervised classification followed by on‐screen visual interpretation/correction, was chosen to delineate the different land and water classes in the Sundarbans region using spatial tools in ArcGIS 10.6. Using a hybrid approach, the errors are eliminated to make sure that land types are classified from coarse‐resolution images with more precision (Rahdari et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have used a hybrid classification approach while using LANDSAT images to delineate the land‐use classes (Kumar, Singh, & Rani, 2013). By adopting a hybrid approach, we eliminate human errors and also make sure that land types are classified with more accuracy from medium resolution images (Rahdari, Soffianian, Pourmanafi, Mosadeghi, & Ghaiumi, 2018). Researchers observed that the hybrid approach could be applied in a regular image processing software package (ERDAS Imagine) to make land‐use maps with higher accuracy from satellite images of moderate spatial resolution, where both discrete and continuous land‐use types occur side by side (Mas et al, 2017).…”
Section: Methodsmentioning
confidence: 99%